Biological effects of Pfaffia glomerata (Spreng.) Pedersen and Pfaffia paniculata (Martius) Kuntze (Amaranthaceae) - Alvim, Nádia Regina (2008)
Pfaffia glomerata (Spreng.) Pedersen. (Amaranthaceae) and Pfaffia paniculata (Martius) Kuntze are native plants found in the flooded area of the islands of Porto Rico, state of Paraná, Brazil. They are used in folk medicine as tonics, aphrodisiacs, and to treat diabetes. The methanolic extract obtained from roots of both species was used to evaluate the molluscicidal activity against the periwinkle Biomphalaria glabrata and the hypoglycemic activity of Pfaffia glomerata was investigated in rats with diabetes induced by alloxan. The saponins from the methanolic extract of P. glomerata and P. paniculata were analyzed by thin-layer chromatography and scum and the hemolitic index was measured. The methanolic extract obtained from Pfaffia glomerata showed higher content of hemolytic saponin than Pfaffia paniculata and presented molluscicidal activity against Biomphalaria glabrata from 200 ppm. However, the treatment with P. glomerata extract did not promote any significant effect on glycemic levels.